On the circulation in the Puerto Morelos fringing reef lagoon - Coronado, C.; Candela, J.; Iglesias-Prieto, R.; Sheinbaum, J.; López, M.; Ocampo-Torres, F. J. (Coral reefs, 2007)
For a period of 22 months beginning in September 2003, an array of four current profilers were deployed on the Puerto Morelos fringing reef lagoon, a microtidal Caribbean environment characterised by the influence of the Yucatan Current (YC) and a Trade Wind regime. The dataset includes water currents, bottom pressure, and surface waves complemented with coastal meteorological data and surface currents from an acoustic Doppler current profiler moored 12 km offshore. Normal circulation conditions consisted of a surface wave-induced flow entering the lagoon over a shallow reef flat and strong flows exiting through northern and southern channels. This wave induced flow was modulated by a low-frequency sea level change related to a geostrophic response to the YC variability offshore, with tidal and direct wind forcing playing additional minor roles. Under extended summer low-wave height conditions, together with a decrease in sea level from the intensification of the offshore current, the exchange of the lagoon with the adjacent ocean was drastically reduced. Under normal wave conditions (H ^sub S^ = 0.8 ± 0.4 m, mean ± SD), water residence time was on average 3 h, whereas during Hurricane Ivan's extreme swell (H ^sub S^ = 6 m) it decreased to 0.35 h.[PUBLICATION ABSTRACT]